Functional characterization and comparative analysis of two heterologous endoglucanases from diverging subfamilies of glycosyl hydrolase family 45 - Berto, Gabriela Leila; Velasco, Josman; Tasso Cabos Ribeiro, Caio; Zanphorlin, Letícia Maria; Noronha Domingues, Mariane; Tyago Murakami, Mario; Polikarpov, Igor; de Oliveira, Leandro Cristante [UNESP]; Ferraz, André; Segato, Fernando (Elsevier, 2019)
Lignocellulosic materials are abundant, renewable and are emerging as valuable substrates for many industrial applications such as the production of second-generation biofuels, green chemicals and pharmaceuticals. However, the recalcitrance and the complexity of cell wall polysaccharides require multiple enzymes for their complete conversion to oligo- and monosaccharides. The endoglucanases from GH45 family are a small and relatively poorly studied group of enzymes with potential industrial application. The present study reports cloning, heterologous expression and functional characterization of two GH45 endoglucanases from mesophilic fungi Gloeophyllum trabeum (GtGH45) and thermophilic fungi Myceliophthora thermophila (MtGH45), which belong to subfamilies GH45C and GH45A, respectively. Both enzymes have optimal pH 5.0 and melting temperatures (Tm) of 66.0 °C and 80.9 °C, respectively, as estimated from circular dichroism experiments. The recombinant proteins also exhibited different mode of action when incubated with oligosaccharides ranging from cellotriose to cellohexaose, generating mainly cellobiose and cellotriose (MtGH45) or glucose and cellobiose (GtGH45). The MtGH45 did not show activity against oligosaccharides smaller than cellopentaose while the enzyme GtGH45 was able to depolymerize cellotriose, however with lower efficiency when compared to larger oligosaccharides. Furthermore, both GHs45 were stable up to 70 °C for 24 h and useful to enhance initial glucan hydrolysis rates during saccharification of sugarcane pith by a mixture of cellulolytic enzymes. Recombinant GHs45 from diverging subfamilies stand out for differences in substrate specificity appearing as new tools for preparation of enzyme cocktails used in cellulose hydrolysis.
Keywords: Cellulases; Enzymatic hydrolysis; Filamentous fungi; Sugarcane bagasse